WAYS TO IMPROVE THE METHODOLOGY OF TAX REVENUE FORECASTING AND PLANNING - Sayidjonov Jamshid Sayidjonovich (Web of Journals Publishing, 2024)
This article presents possible prospects for increasing tax revenues by improving tax administration, factors affecting the increase / decrease in budget revenues, the main directions of tax reform, as well as relevant proposals and recommendations for increasing tax revenues to the state. budget.
Keywords: consolidated budget, import, inflation, direct tax, tax administration, resource taxes, recycling fee, electronic invoices, special control marks based on QR codes.